2019
DOI: 10.1177/1076029619883946
|View full text |Cite
|
Sign up to set email alerts
|

Deep Vein Thrombosis in Europe—Health-Related Quality of Life and Mortality

Abstract: Objectives: Deep vein thrombosis (DVT) is a major health-care burden in Europe, but exact estimates are lacking. This study reports results from the PREFER venous thromboembolism (VTE) study concerning health-related quality of life (HrQoL) and mortality of patients with DVT. Methods: PREFER VTE was a prospective, observational study, conducted in 7 European countries, designed to provide data concerning treatment patterns, resource utilization, mortality, and QoL. First-time or recurrent patients with DVT wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 17 publications
0
38
1
Order By: Relevance
“…5,10,[12][13][14]23,28,29 The pooled frequency of recurrent VTE-related deaths among all causes of deaths was 7.9% (eight studies, 805 deaths, 95% CI: 3.9-13.1; I 2 ¼ 72.9%, p-Egger: 0.84). 5,10,[12][13][14]23,28,29 Two studies reported frequency of cardiovascular death in patients with VTE and in controls without VTE. 11,26 The pooled frequency of cardiovascular death in controls was 0.3% (two studies, 48,946 patients, 95% CI: 0.03-0.95;…”
Section: Frequency and Incidence Of Cardiovascular Deathmentioning
confidence: 99%
“…5,10,[12][13][14]23,28,29 The pooled frequency of recurrent VTE-related deaths among all causes of deaths was 7.9% (eight studies, 805 deaths, 95% CI: 3.9-13.1; I 2 ¼ 72.9%, p-Egger: 0.84). 5,10,[12][13][14]23,28,29 Two studies reported frequency of cardiovascular death in patients with VTE and in controls without VTE. 11,26 The pooled frequency of cardiovascular death in controls was 0.3% (two studies, 48,946 patients, 95% CI: 0.03-0.95;…”
Section: Frequency and Incidence Of Cardiovascular Deathmentioning
confidence: 99%
“…The most commonly reported DVT symptoms included pain and swelling, with over 72% and 54%, respectively, across all countries. The baseline characteristics of the total sample and cancer subgroup can be found elsewhere [9].…”
Section: Patients Characteristicsmentioning
confidence: 99%
“…Specific attention is given to the differences per country, the difference between patients with active cancer and those without and the association between the burden of the disease and baseline patient characteristics. A separate paper concerning mortality and health related quality of life of patients with DVT is available elsewhere [9].…”
Section: Introductionmentioning
confidence: 99%
“…Elective Total Hip Arthroplasty (THA) surgery has proven to be a reliable and effective surgical procedure, with widely reported satisfactory clinical outcomes . Venous Thromboembolism (VTE), encompassing Deep Vein Thrombosis (DVT) and Pulmonary Embolism (PE), presents a substantial burden of disease, both in terms of health-related quality of life and long-term mortality 1 . VTE is a result of peripheral vein thrombosis (DVT), leading to embolisation and thrombosis of a segmental branch of the pulmonary artery (PE) 2 .…”
Section: Introductionmentioning
confidence: 99%